Investigating diet to control asparagine uptake as an adjunct to asparaginase treatment - Forbrigger, Zara; MacDonald, Tamara; Kulkarni, Ketan; Stadnyk, Andrew W. (Frontiers in Oncology, 2026)
Ongoing refinements of multidrug regimens, and particularly the addition of L-asparaginase, resulted in an immediate gain in survival for pediatric acute lymphoblastic leukemia patients. Yet L-asparaginase has substantial side effects which may require dose reductions or delays in subsequent doses. There are at least 3 possible sources of L-asparagine to consider when balancing blood levels with asparaginase dosing, diet, cell synthesis and bacterial synthesis. To date, there is one precedent, in mice, in which blood L-asparagine levels are reduced as a consequence of reducing consumed levels. We build on that approach in experiments aimed at testing whether long-term dietary restriction of L-asparagine and possibly gut bacteria can impact blood levels. In our experiment, 2 groups of mice received food pellets with either 4% or 0% L-asparagine. Blood and fecal metabolites and fecal bacteria were sampled over 72 days. After this accommodation period, all mice continued their diet and received a single injection of pegylated E. coli recombinant L-asparaginase. Samples for bacteria and metabolites were collected 4 and 5 days later, respectively. Neither diet had adverse effects on the general health of the mice nor did diet alone change blood L-asparagine levels. Both diets led to changes in gut bacteria. L-asparaginase depleted blood L-asparagine in mice consuming either diet. Bacteria identified in fecal pellets revealed that the microbiomes of mice in the 2 cages were different (cage effect) and remained different although metagenomic analyses of day 72 feces indicated there were no diet-dependent differences in bacterial asparaginase or asparagine synthetase. These outcomes indicate that mice recover from any short-term down regulation of blood L-asparagine due to diet and consequently the metabolic controls become complex, and the gut microbes seem to not be a great influence. Further research should include approaches to determine the source of L-asparagine in the blood while ingesting diets with no/low or high amounts of L-asparagine.